An effective approach to alleviating the thermal effect in microstripe array-LEDs via the piezo-phototronic effect. Issue 1 (7th December 2017) - Du, Chunhua; Jing, Liang; Jiang, Chunyan; Liu, Ting; Pu, Xiong; Sun, Jiangman; Li, Dabing; Hu, Weiguo
Abstract : Thermal failure in high-power LEDs is effectively alleviated via the piezo-phototronic effect. Abstract : Micro-LEDs, with unparalleled high brightness compared to conventional LEDs and OLEDs, have been regarded as a research priority for high-power light emitting diodes. Thermal issue is an inevitable concern in LED operation, leading to luminescence degradation and lifetime shortening. Here we studied the role the piezo-phototronic effect played in the luminescence enhancement of microstripe array-LEDs via strain compensation at room temperature. And also, we firstly reveal the effective modulation of the piezo-phototronic effect on luminescence characteristics at high temperatures via EL measurements with the temperature increasing from 300 K to 380 K. Industrial GaN-based high-power LEDs have been reported to be commonly operated in the temperature range of 70–90 °C. Compared to at 300 K, the integrated EL intensity at 364 K decreases to 67.8% without strain; however, by applying a strain of 0.09%, it is demonstrated to rise to as high as 104% of that at 300 K. This work deepens the understanding of the high-temperature piezo-phototronic effect and will give significant guidance for high-power LEDs from the important direction of nitride semiconductors.